Can governance be ethical if it is not diverse?. (January 2022) - Porritt, Vivienne; Stagg, Fee
Can governance be ethical if it is not diverse? Abstract There is growing acceptance that governing boards in English schools and academies should be diverse. Yet progress towards this strategic aim remains slow despite initiatives to address this. We ask whether boards represent their communities and whether they model diverse and ethical leadership as seen in the culture and values of a school or trust and through recruitment and we argue that governance cannot be ethical if it is not diverse. Our thinking about the question at the heart of this paper is influenced by ethical leadership as well as the Black Lives Matter movement. We draw on two diverse boards, one a maintained governing board for a primary school and the other a Multi-Academy Trust board, to support our opinion and thank them for sharing their challenges and successes. We suggest ways forward to deliberately disrupt the status quo and ensure governing boards represent the students in their communities.